PENYULUHAN KESEHATAN REPRODUKSI PADA REMAJA DI SMK SWASTA YAPIM BIRU-BIRU - Firdaus Fahdi; Herviani Sari; hengki frengki manulang; Bahtera Bindavid Purba (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Reproductive health is an important issue and must get attention, especially among adolescents. Adolescence is a transition period from childhood and adulthood, in this period a growth spurt occurs, secondary sex characteristics arise, fertility is achieved and psychological and cognitive changes occur. Adolescence occurs in the age range of 10-19 years. This period is the period of maturation of the human reproductive organs, and is often called puberty. During adolescence, children experience accelerated growth both physically and psychologically. During this period, namely the transition from children to adolescents, there are three risks that are often faced by adolescents, namely risks related to sexuality (unwanted pregnancy, abortion and infection with sexually transmitted diseases), drug abuse, and HIV/AIDS. Therefore, our research team feels the need to provide education to students at school. Community service activities regarding reproductive health are carried out at the Yapim Biru-biru Private School through 3 stages, namely the preparation stage, implementation stage and reflection stage. At the end of this activity, at the reflection stage, a questionnaire was distributed as a form of evaluation to see the understanding that had been obtained after participating in this activity. The results of this service activity provide benefits in the form of expanding the horizons and knowledge of adolescents about reproductive health, so that adolescents can be more alert and careful in socializing.